2021
DOI: 10.1167/iovs.62.6.15
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral Visual Impairment Characterized by Abnormal Visual Orienting Behavior With Preserved Visual Cortical Activation

Abstract: PURPOSE.Children with cerebral visual impairment (CVI) often have abnormal visual orienting behaviors due to impaired or damaged visual cortex. Alternatively, visualcortical function is intact but visual information is not transformed downstream into an appropriate oculomotor output (visuomotor dysfunction). We examined visual, anatomic, and oculomotor assessments to distinguish visuomotor dysfunction from CVI associated with severely reduced visual-cortical response. METHODS.We reviewed the medical records fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 49 publications
0
12
0
Order By: Relevance
“…Ref (Clarke et al, 1997) Low GRADE In VEP stimulation in CVI an abnormal response was found often, especially at the occipital pattern VEP (more than temporo -parietal pattern VEP). Ref (Frank et al, 1992) Moderate GRADE A subset of patients with CVI have abnormal visual orienting behaviors despite a normal VEP (visuomotor dysfunction; Kelly et al, 2021) Very low GRADE Sweep VEP nearly always deviating from normal controls, only in 16% of children with CVI a normal (straight) eye position was found. In CVI usually strabismus is found as well as motility disorders of the eyes.…”
Section: Very Low Gradementioning
confidence: 99%
“…Ref (Clarke et al, 1997) Low GRADE In VEP stimulation in CVI an abnormal response was found often, especially at the occipital pattern VEP (more than temporo -parietal pattern VEP). Ref (Frank et al, 1992) Moderate GRADE A subset of patients with CVI have abnormal visual orienting behaviors despite a normal VEP (visuomotor dysfunction; Kelly et al, 2021) Very low GRADE Sweep VEP nearly always deviating from normal controls, only in 16% of children with CVI a normal (straight) eye position was found. In CVI usually strabismus is found as well as motility disorders of the eyes.…”
Section: Very Low Gradementioning
confidence: 99%
“…Typical clinical features of CVI may be manifest in a child, despite undetected brain signatures. Even adults with visual field loss following stroke, can show normal MRI brain imaging in 30% of cases ( Zhang et al, 2006a , b ; Kelly et al, 2021 ), as can around 12% of children with Cerebral Palsy (CP) ( Robinson et al, 2009 ; Towsley et al, 2011 ). It is therefore important to acknowledge that a report of a “normal” brain MRI in a child with neurovisual impairment does not exclude the diagnosis of CVI.…”
Section: The Differences Between Typical Vision and Cortical Or Cerebral Visual Impairmentmentioning
confidence: 99%
“…Many patterns of visual disorder can be seen, with each affected child having their own unique form of vision ( Philip and Dutton, 2014 ). Depending on the topography and extent of the pathology, the deficit may impair any aspect of visual function affecting central vision, peripheral vision (in all or part of the visual field), movement perception, gaze control, visual guidance of movement, visual attention, attentional orientation in space, visual analysis and recognition, visual memory and spatial cognition, as well as central vision, the visual fields, visual analysis, visual exploration, visual attention, or visual memory ( Kelly et al, 2021 ), in any combination, or degree. Recognition or visual memory of an object, a face or a place, the act of processing a set of stimuli or a complex scene, or difficulties directing movement or gesture under the control of vision, can be impaired in a variety of combinations.…”
Section: The Differences Between Typical Vision and Cortical Or Cerebral Visual Impairmentmentioning
confidence: 99%
See 2 more Smart Citations